Engagement and Awareness of Islamic Banking Customers: Exploring an African Context - Riyad Moosa (UIN Sunan Gunung Djati Bandung, 2023)
The Islamic banking industry is a niche market within the South African banking industry. Information is needed on the profile of customers and their level of awareness concerning activities at Islamic banks. Thus, this study aims to identify the banking engagements and CSR awareness levels of Islamic bank customers in South Africa. This study involved 163 respondents in South Africa selected using non-probability sampling. Meanwhile, the data were collected using a questionnaire. The collected data were then analyzed using descriptive statistics. The results indicate that respondents seek Islamic banking for them, have a long-standing relationship with the Islamic bank, and mainly use saving, current, and investment accounts. The findings also show that respondents should be aware of the CSR activities undertaken by the Islamic banks, and they could have engaged in CSR activities more regularly. Thus, the Islamic bank management is encouraged to proactively make their Sharia-compliant offerings and CSR activities visible.